Report on the Observance of Standards and Codes on Accounting and Auditing Update : Republic of Serbia - World Bank Group (World Bank, Vienna, 2016)
This report on observance of standards and codes in accounting and auditing (ROSC A & A) provides an assessment of accounting, financial reporting, and auditing requirements and practices within the enterprise and financial sectors of Serbia and sets forth areas of consideration with a view to improving the country’s institutional environment for corporate financial reporting. To assess Serbia’s compliance with standards and codes, this report uses international benchmarks of good practice, including international financial reporting standards (IFRS), international standards on auditing (ISA), the statements of membership obligations (SMO) of the international federation of accountants (IFAC), and - because Serbia is seeking accession to the European Union (EU) - relevant provisions of the EU acquis communautaire (the acquis) governing financial reporting. The assessment focuses on the strengths and weaknesses of the A and A environment that influence the quality of corporate financial reporting, and includes a review of both statutory requirements and actual practice. It updates an earlier assessment published in 2005. ROSC A and A assess accounting and auditing practices in participating countries.